Survei Motivasi Belajar Siswa Kelas X Dalam Mata Pelajaran PJOK SMA Keberbakatan Olahraga Bahteramas Sulawesi Tenggara - Jumiati, Basman, Resky Ana Abadi (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2024)
The aim of this research is to determine the learning motivation of Class Based on the results of the research and discussion above, the results of research at the Bahteramas Sports Gifted School, Southeast Sulawesi on July 25 2024. Research has been carried out on the learning motivation of class person. This research is used to carry out measurements with the aim of producing accurate data.